NARRATIVE DIDACTISM OF ULIANA KRAVCHENKOS COLLECTION «SNOWDROPS» - Волощук, Г. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Narratological, figurative and plot structure levels of selected works from the collection Snowdrops aimed at children and young people have been studied in the paper. The distinctive feature of the works under scrutiny is the indissolubility of enlightenment, realistic and neoromanticism ways of the author’s aesthetic influence on the reader.